Correlation of mechanical performance and morphological structures of epoxy micro/nanoparticulate composites - Dong, Yu; Chaudhary, Deeptangshu; Ploumis, Charlie; Lau, K. (Pergamon, 2011)
Epoxy composites reinforced with zinc oxide nanoparticles, alumina microparticles and nanoclays at 1, 3, 5 and 8 wt% were fabricated by combined mechanical stirring and ultrasonication processes. The reinforcement efficiency was determined from the composite flexural and impact properties with the correlation to the morphological structure and interfacial bonding effect via scanning electron microscopy (SEM) and X-ray diffraction (XRD). The results reveal the moderate enhancement of composite modulus up to a maximum 27% for 8 wt% alumina inclusions; flexural strengths increase quite marginally or even show a decreasing trend with increasing the particle content by weight. The comparison between a series of mathematical models and experimental data of flexural moduli indicates the applicabilities of Paul model for alumina and zinc oxide reinforcements, and Kerner model and Ishai–Cohen model for nanoclays. The appropriate micro/nanoparticle selection due to different shapes and sizes is critical for the better mechanical performance of their composite materials.